Navigating puberty with special needs teenagers: empowering parents through a sexuality education workshop - Padma A. Rahman; Akehsan Dahlan; Nur Atiqah Azman; Selamat, S. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Adolescence is a crucial phase of development, marked by significant physical, emotional, and social changes. Navigating these changes for teenagers with special needs can be particularly challenging. Addressing these topics is essential to ensure holistic well-being and healthy development of teenagers with special needs. This workshop aimed to equip parents with the necessary knowledge, skills, and strategies to navigate conversations about puberty and sexuality effectively. This paper is to present the findings of this workshop focused on puberty and sexuality education for parents of teenagers with special needs. A diverse group of parents of teenagers with special needs were recruited through Facebook groups, special schools, and community organizations. Prior to the workshop participants were invited to answer questions regarding their concerns about their special needs child sexuality. A total of 150 parents responded to this qualitative survey. The workshop includes a slot for a sexuality education lecture and a hands-on practical session focusing on managing menstruation and masturbation. A total of 69 participants for the workshop were required to answer pre and post-questionnaires – to determine the knowledge, perceptions, dedication, and willingness in delivering sexual information to teenagers with special needs.